1986
DOI: 10.1113/jphysiol.1986.sp016225
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of sympathetic neurone activity during expiration in the cat.

Abstract: SUMMARY1. The properties of sympathetic preganglionic neurone activity during expiration were studied in pentobarbitone-anaesthetized (n = 26) and in non-anaesthetized, mid-collicular decerebrate (n = 5), paralysed, artificially ventilated cats in which the electrical activity of the phrenic nerve and of the cervical sympathetic trunk was recorded.2. In control conditions (end-tidal Pco, between 35 and 40 mmHg, zero endexpiratory pressure) sympathetic activity during expiration was either steady at a low level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…After vagotomy, however, most of the inspiratory-related inhibitory phase is removed and sympathetic activity actually rises throughout this phase, peaking at end inspiration. 8,9,27 To test the role of vagal feedback in humans, we used the heart-lung transplant patient as a model of pulmonary vagal denervation. Lung transplantation interrupts the pulmonary branch of the vagus nerve but retains a native tracheal remnant above the carina.…”
Section: Discussionmentioning
confidence: 99%
“…After vagotomy, however, most of the inspiratory-related inhibitory phase is removed and sympathetic activity actually rises throughout this phase, peaking at end inspiration. 8,9,27 To test the role of vagal feedback in humans, we used the heart-lung transplant patient as a model of pulmonary vagal denervation. Lung transplantation interrupts the pulmonary branch of the vagus nerve but retains a native tracheal remnant above the carina.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which each type of vagal inflation afferent participated in the synchronization of SND to ITP and the entrainment of PNA to lung inflation remains unclear. Nonetheless, whether the afferents are the same or different, our results provide new information on the question of whether vagal lung inflation afferent activity alters SND not only indirectly via their actions on respiratory networks but also via a more direct pathway to sympathetic neurons (4,59).…”
Section: Ltf and Vagal Lung Inflation Afferentsmentioning
confidence: 94%
“…There are at least two sources of respiratory modulation of SND: input from vagal lung inflation afferents and an influence of the respiratory rhythm generator on central sympathetic neurons (4 -6, 21, 25, 33-35, 59). Although some investigators (38,49) have proposed that there is a common network controlling both respiratory and cardiovascular functions, others have suggested that cardiorespiratory synchronization reflects both the direct coupling of two distinct central networks and shared input from peripheral afferents (4,6,21,59).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Whether this represented early inspiratory depression (Bainton et al 1985) or the end of a period of expiratory excitation (Bachoo & Polosa, 1986) was not determined.…”
Section: Discussionmentioning
confidence: 99%